Teacher Agency in the Development of Integrated Science Curriculum: A Case Study in Elementary School (Universitas Pendidikan Indonesia (UPI), 2026)
The development of a STEAM integrated science curriculum within the Merdeka Curriculum demands a high level of teacher agency because teachers play a direct role in translating curriculum policies into classroom learning practices. This study aims to analyse the agency of classroom teavhers in the development of STEAM integrated science curriculum, including their perceptions, teaching, and the challenges and supporting factors for its implementation. The research uses a qualitative approach with a case study design. The research subject is one elementary school teacher who has implemented STEAM based science learning. Data collection techniques include in-depth interviews, classroom observation, reflective questionnaires, and analysis of learning documents. Data analysis was conducted through data reduction, data presentation, and coclusion drawing, with data validity maintained through source and technique triangulation. The research findings indicate that teachers have a positive perceptions of STEAM integration and demonstrate strong agency through autonomy in adapting the curriculum, developing contextual teaching modules, and implementing project-based learning and simple experiments. However, the implementation of STEAM still faces obstacles such as limited facilities, time, and conceptual understanding of STEAM. The conclusion of this study confirms that the success of integrated STEAM science curriculum development is highly influenced by teacher agency, supported by curriculum flexibility, professional collaboration, and technological support